2012
DOI: 10.1038/leu.2011.386
|View full text |Cite
|
Sign up to set email alerts
|

A role for Danazol in chronic lymphocytic leukemia

Abstract: The clinical management of chronic lymphocytic leukemia (CLL) patients with fludarabine-resistant disease or tumor cells with 17p deletions remains problematic. 1 High-dose glucocorticoids (HDGCs) are among the most effective treatment approaches for such patients, as well as elderly patients who cannot tolerate conventional chemotherapy. However, HDGCs are not without significant side effects and are only palliative in nature. 2 Identification of nontoxic agents that could improve the therapeutic efficacy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…Based on these properties of danazol, we assessed its effects on leukemic cells derived from CLL patients. Consistently with the observations of Tung et al [ 19 ], we showed that danazol-induced caspase-dependent apoptosis and cytotoxicity of CLL cells in the peripheral blood and bone marrow. Danazol-induced apoptosis appears to involve both mitochondrial and membrane cascades because of similar levels of active caspase-9 and active caspase-8 expressions detected in leukemic cells.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Based on these properties of danazol, we assessed its effects on leukemic cells derived from CLL patients. Consistently with the observations of Tung et al [ 19 ], we showed that danazol-induced caspase-dependent apoptosis and cytotoxicity of CLL cells in the peripheral blood and bone marrow. Danazol-induced apoptosis appears to involve both mitochondrial and membrane cascades because of similar levels of active caspase-9 and active caspase-8 expressions detected in leukemic cells.…”
Section: Discussionsupporting
confidence: 93%
“…However, the role and the mechanism of action of danazol in these cases are unclear. Danazol-induced apoptosis of CLL cells was first described by Tung et al [ 19 ]. The authors studied patients receiving danazol in combination with glucocorticoids and showed a significant decrease in the leukocyte count, which increased after withdrawal of this drug.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations